Prolonged (>100 Ma) ultrahigh temperature metamorphism in the Napier Complex, East Antarctica: A petrochronological investigation of Earth's hottest crust - Clark, Christopher; Taylor, Richard; Kylander-Clark, A.; Hacker, B. (Wiley - Blackwell, 2018)
The Napier Complex in East Antarctica preserves a record of ultrahigh temperature (UHT) metamorphism during the late Archean to early Palaeoproterozoic. While there is little argument that the UHT metamorphic event began at c. 2,580 Ma, the duration over which the rocks resided at UHT has been the subject of intense debate, with estimates for the end of metamorphism ranging from 2,545 to 2,440 Ma—a discrepancy of some 105 Ma. To resolve the time-scale of UHT metamorphism, a zircon and garnet petrochronological (U–Pb, REE and Ti) data set from a suite of rocks from the Tula Mountains region of the Napier Complex was analysed. Individual concordant populations define zircon U–Pb ages for (a) reset zircon cores of 2,502–2,439 Ma; (b) zircon rims of 2,491–2,454 Ma; and (c) neocrystallized sector-zoned zircon from 2,492 to 2,443 Ma. Ti-in-zircon thermometry places a minimum estimate of 830°C for zircon crystallization, with the majority of concordant populations yielding temperatures >900°C. Zircon–garnet partitioning (DYb vs. DYb/Gd) arrays reveal that the bulk of metamorphic zircon defines an equilibrium relationship with the garnet that forms part of the peak assemblage. Combined with existing geochronological constraints, the new petrochronological data demonstrate that the Napier Complex remained at UHT from c. 2,585 Ma until at least 2,450 Ma, a residence time of 135 Ma. In the absence of evidence for contemporaneous emplacement of large volumes of igneous rocks, a number of factors likely combined to drive and maintain these extreme temperatures. We propose that the P–T conditions experienced by the Napier Complex were achieved through a combination of orogenic plateau formation, preconditioning of the crust by a high-T magmatic and UHT metamorphic event at c. 2,850 Ma, inefficient removal of heat-producing elements during partial melting and slow exhumation. This style of long duration, regional, extreme metamorphism is becoming more commonly identified in the rock record as larger and more robust data sets are collected (e.g. the Eastern Ghats of India and the Gondwanan East African Orogen) and is commonly associated with the amalgamation phases of supercontinents/cratons.